Crowdfunding and accounting history: The construction of the Gran Madre di Dio Church (Turin, 1814 - 1832) - Sinicropi, Silvia; Cortese, Damiano; Pollifroni, Massimo; Cantino, Valter (De Computis, Revista Española de Historia de la Contabilidad., 2020)
This study emphasizes the history of accountancy, shedding light on its link with artistic and cultural patrimony, an issue that is scarcely addressed but is nearly always a matter underlying the greatest monuments of our civilization. As a case study, this study focuses on one of the significant architectural monuments of the City of Turin: the “Church of Gran Madre di Dio”; which was built to celebrate a historical and political event. Today it is a place of worship, a tourist attraction and a pilgrimage site. The current study corrects, from an accounting and historical perspective, the paucity of knowledge related to the Church of “Gran Madre di Dio”, and it also highlights the social impact its construction had upon the Turin area.